The Influence of Intellectual Capital, Profitability, Institutional Shareholding and Board Size on Company Value (Empirical Analysis of the Consumer Goods Industry Listed on the Indonesia Stock Exchange 2019–2023) - Uji Nurhayati, Unggul; Ismail, Tubagus; Irawati, Irawati (DINASTI RESEARCH, 2025)
This research purpose to analyze the impact of intellectual capital, profitability, institutional shareholding, and board size based on the value of consumer goods industry companies. The population consisted of all consumer goods industry companies registered on the Indonesia Stock Exchange from 2019 until 2023. This study used purposive sampling technique and obtained 170 observation data. The data analysis process uses panel data linear regression, and is processed using E-Views 12 version. This research show that knowledge-based assets significantly influenced company valuation, financial performance significantly affected company valuation, managerial shareholding had no significant impact on firm valuation, and board size did not significantly affect company value.